Distraction Guided Imagery Technique to Reduce Anxiety Levels in Elderly with Hypertension - Agustina, Marisca (GLOBAL HEALTH SCIENCE GROUP, 2024)
Elderly is an aging process with increasing individual age characterized by a decrease in the function of organs such as the brain, heart, liver and kidneys and increased loss of active body tissue in the form of body muscles. The decline in organ function in the elderly is due to a decrease in the number and ability of body cells, so that the ability of body tissues to maintain normal function disappears, so they cannot defend against infection and repair damage suffered (Fatmah, 2010). The purpose of this study was to identify the Guidance Imagery Distraction Technique on Reducing Anxiety Levels in Elderly People with Hypertension in Rt 010 / Rw 005 Lenteng Agung South Jakarta Year 2023.This type of research uses a quantitative type research design with a research design using pre-experiment. The population in the study was elderly with hypertension as many as 39 people in RT 010 / RW 05 Lenteng Agung The sample technique used was putposive sampling and data analysis using paired sample t-test. The results of this study indicate that after being given guided imagery techniques, the majority experienced a decrease in anxiety levels, namely mild anxiety as many as 11 elderly people (73.3%) and respondents who experienced moderate anxiety as many as 4 elderly people (46.7%). anxiety in elderly people with hypertension in RT 010 In RT 010 /RW 05 Lenteng Agung before being given the Guided Imagery distraction technique, the majority experienced severe anxiety. Anxiety in the elderly with hypertension in RT 010 / RW 05 Lenteng Agung before being given the Guided Imagery distraction technique, the majority experienced mild anxiety. There is an effect of Guidance Imagery distraction techniques on reducing anxiety levels in the elderly with hypertension in RT 010 / Rw 005 Lenteng Agung, South Jakarta in 2023.